Mental health assistance: identification of nursing diagnoses in a community mental health service - Eurides Santos Pinho; Adrielle Cristina Silva Souza; Ana Caroline Gonçalves Cavalcante Moreira; Luzana Eva Ferreira Lopes Nogueira; Amanda Melo e Santos Limongi; Nathália dos Santos Silva; Johnatan Martins Sousa (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: to map and identify nursing diagnoses targeted at night care users in a Psychosocial Care Center according to NANDA-I Taxonomy. Method: this is a descriptive-exploratory study, of documentary research type of 319 records in medical records. It was held in a Psychosocial Care Center III in Goiás, from 2014-2018. Nursing diagnoses and records were extracted with non-standardized language. Results: 813 records of nursing diagnoses identified in 53 different titles, in 10 domains, were identified. The most frequent diagnosis was risk for self-extermination. The domain with the highest number of diagnostic records was activity/rest. There was a predominance of diagnoses focused on the problem. Final considerations: mapping contributes to the planning of evidence-based nursing interventions and to the strengthening of professional identity in mental health. It is evident the need for practices that go beyond the symptoms in a preventive perspective, with a view to comprehensiveness.